2023
DOI: 10.1186/s12974-023-02941-4
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell RNA sequencing unveils Lrg1's role in cerebral ischemia‒reperfusion injury by modulating various cells

Zhaohui Ruan,
Guosheng Cao,
Yisong Qian
et al.

Abstract: Background and purpose Cerebral ischemia‒reperfusion injury causes significant harm to human health and is a major contributor to stroke-related deaths worldwide. Current treatments are limited, and new, more effective prevention and treatment strategies that target multiple cell components are urgently needed. Leucine-rich alpha-2 glycoprotein 1 (Lrg1) appears to be associated with the progression of cerebral ischemia‒reperfusion injury, but the exact mechanism of it is unknown. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Based on previous work that correlated cell maturity levels with microglia activation-related gene expression, a score was generated for genes involved in glial metabolism, pro-inflammatory activation (M1), and anti-inflammatory activation (M2) ( Supp. Table 12 ) 72 . The score was generated by dividing the number of transcripts for each gene of interest by the total transcripts for each nucleus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous work that correlated cell maturity levels with microglia activation-related gene expression, a score was generated for genes involved in glial metabolism, pro-inflammatory activation (M1), and anti-inflammatory activation (M2) ( Supp. Table 12 ) 72 . The score was generated by dividing the number of transcripts for each gene of interest by the total transcripts for each nucleus.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the differences between the subclusters, M1, M2, and metabolism scores were again generated as described above ( Supp. Table 12 ) 72 . No significant differences between exercise and sedentary groups or between subclusters were observed ( Supp.…”
Section: Resultsmentioning
confidence: 99%
“…However, whilst new vessels were observed which may confer survival benefit, the likelihood is that these penumbral vessels are dysfunctional compromising their beneficial effect ( 110 ). A more recent study employing a cerebral ischemia-reperfusion injury model in the mouse demonstrated that in the Lrg1 −/− mouse there was reduced cerebral oedema and infarct size, which was accompanied by improvement in neurological function ( 111 ). Crucially, this study showed that following cerebral ischaemia, cells of the blood-brain barrier were able to retain the expression of barrier function related genes, such as claudin 11, integrin β5, protocadherin 9, and annexin A2, more effectively in the absence of LRG1 ( 111 ).…”
Section: Lrg1 Ischemia and Strokementioning
confidence: 99%
“…A more recent study employing a cerebral ischemia-reperfusion injury model in the mouse demonstrated that in the Lrg1 −/− mouse there was reduced cerebral oedema and infarct size, which was accompanied by improvement in neurological function ( 111 ). Crucially, this study showed that following cerebral ischaemia, cells of the blood-brain barrier were able to retain the expression of barrier function related genes, such as claudin 11, integrin β5, protocadherin 9, and annexin A2, more effectively in the absence of LRG1 ( 111 ). This demonstrates that LRG1 has a detrimental effect on the blood-brain barrier and thus contributes to vasogenic cerebral oedema.…”
Section: Lrg1 Ischemia and Strokementioning
confidence: 99%
“…weaken barrier [113] -ECL1-G60R, human channelopathy: Cl -/small molecule flux [115] -transferred from BEC to leukocytes in EAE, possibly supporting transmigration into CNS [116] -Thr(207)-phosphorylation opens porcine BBB, protein kinase A [117] -TGF-β/activin signalling increases Cldn5 [118] -VE-cadherin via Akt-activation: phosphorylation of FoxO1 induces Cldn5 [119] -adrenomedullin: enhanced expression and TER, decreases permeability [112] -increase (mRNA, protein, promoter): gluco-corticoids TER up [120,121], estrogen [122] -ROCK via EphA2: down-regulation [123] -ROCK up in dementia: Cldn5 down [124] -C/EBP-α (stimulated by JAM-A) up-regulation, reduced permeability [125] -serum Cldn5 up: autistic children [126], severe stroke [127] -down-regulated by EphA4/Tie2/Akap12 signalling mediating microvascular dysfunction and trauma [128] -down-regulated at low Cu [94] -oxidative stress inhibitor improves Cldn5, ZO-1, TER via Nrf2/HO-1 [129] Claudin-11 (Oligodendrocyte-specific protein) -gene CLDN11, chromosome 3 (human), 3 (mouse) -mRNA/protein: very high expression in BEC (human, mouse, rat) in vivo equal to Cldn5, in vitro strongly down-regulated [50,130] -less expressed in human brain oligodendrocytes [50] -KO mouse: mild neurological deficits [131], deafness (low endocochlear potential) [47] -KD: enhanced dextran permeability through BEC layers [130] -contributes to tightness of BEC layers [50,130] and BBB [132] -207 aa; M.W., 22.0 Da; pI, 8.22; N-/C-terminal tail, 1/29 aa; ECL1/ECL2, 50/14 aa (human) -very strong homophilic cis/trans interaction (Cldn11 >> other Cldns, Ocln, Tric [55,133]) -no heterophilic binding [55]; Cldn5 colocalisation in junctions [50,130] -continuous P-face oriented TJ-s...…”
Section: Tight Junctions: Proteins Functions and Structuresmentioning
confidence: 99%